Macroeconomic determinants of workers' remittances: Host versus home country's economic conditions. - Vargas-Silva, C; Huang, P (Routledge, 2006)
This study examines the determinants of worker's remittances. Variance decompositions, impulse response functions and Granger causality tests derived from a vector error correction model are used to test if remittances are affected by the macroeconomic conditions of the host (remittance sending) or home (remittance receiving) country. Data from Brazil, Colombia, the Dominican Republic, El Salvador, Mexico and the US are used. The results indicate that remittances respond more to changes in the macroeconomic conditions of the host country, than to changes in the macroeconomic conditions of the home country.